EFFECT OF STRENGTH TRAINING, FUNCTIONAL TASK RELATED TRAINING AND COMBINED STRENGTH AND FUNCTIONAL TASK RELATED TRAINING ON UPPER EXTREMITY IN POST STROKE PATIENTS (International Journal of Physiotherapy, 2017)
Background: Weakness presents serious compromise to movement function in hemiplegics. Despite the correlation between weakness and impaired function, a clear relationship between strength and function needs more exploration. This study evaluated compared to strength and functional training alone with combined strength and functional training in rehabilitation of upper extremity in stroke patients.Methods: Forty-five patients with history of stroke of duration 3weeks-6months who could initiate shoulder flexion, abduction, elbow flexion and extension, wrist and finger movements were included in the study and randomized into three groupsGroup-I - Strength-trainingGroup-II - Functional-task-related trainingGroup-III - Combined Strength and Functional-task-related training for the upper extremityPatients with cognitive impairments, musculoskeletal complications and with the previous history of hemiplegia wereexcluded.Outcome Measures used: Fugl-Meyer, Chedoke-Arm and Hand-Inventory, Dynamometer and MMT Interventions were given 3days/week for 6weeks. Subjects were evaluated at 0, 3 and 6weeks.Result: All the three groups showed improvements in Fugl-Meyer (p